Duas novas espécies de Polietina Schnabl & Dziedzicki (Diptera, Muscidae) do Brasil - Couri,Márcia Souto (1995)
Polietina nigra, sp.n. from Una, Bahia and Rio de Janeiro and Polietina univittata. sp.n. from Curitiba, Paraná and Rio de Janeiro are described from adults and P. nigra also from the mature third instar larvae.